Morfometría del epitelio intestinal de pollos Cobb 500 por efecto de adición alimentaria con extracto acuoso de orégano (Origanum vulgare, L) - Zambrano Sánchez, Ángela Mariela (2021)
The objective of this research was to determine by morphometry of the intestinal epithelium in COBB 500 chickens the effect of the addition with aqueous extract of oregano (Origanum vulgare, L). The used experimental design was a completely Randomized design with 5x2 Factorial Arrangement, T0 (commercial AEO), T1 (growth-promoting antibiotic), where Factor A represented oregano oil inclusion levels (T2 100 ppm, T3 200 ppm, T4 300 ppm), in addition to factor B, which was the effect of sex. For the study of the data, the analysis of variance was used through the statistical packages InfoStat (2019) and an alpha value of 5%. As a result, significant differences were found between sex and treatments at day 21 (p <0.05) for villi width and crypt depth, where for males T4 (300 ppm) and for females T1 (APC) presented the values higher efficiency. Likewise, at day 42, significant difference for the three variables under study (p <0.05), where for males and females the T3 (200 ppm) presented higher values of villus height with 1.11 mm, and 1.02 mm and for the depth of the crypt the T1 APC and T2 100 ppm presented the lowest values with 0.15 mm. It is concluded that the addition of essential oils of oregano constitutes a viable alternative for the replacement of APC, being a natural nutritional promoter that positively improves the morphology of the villi (longer and wider) and crypts (less deep and wide) in Cobb500 chickens.